Ultrahigh green and red optical gain cross sections from solutions of colloidal quantum well heterostructures - Delikanli, Savas (2021)
We demonstrate amplified spontaneous emission (ASE) in solution with ultralow thresholds of 30 μJ/cm2 in red and of 44 μJ/cm2 in green from engineered colloidal quantum well (CQW) heterostructures. For this purpose, CdSe/CdS core/crown CQWs, designed to hit the green region, and CdSe/CdS@CdxZn1–xS core/crown@gradient-alloyed shell CQWs, further tuned to reach the red region by shell alloying, were employed to achieve high-performance ASE in the visible range. The net modal gain of these CQWs reaches 530 cm–1 for the green and 201 cm–1 for the red, 2–3 orders of magnitude larger than those of colloidal quantum dots (QDs) in solution. To explain the root cause for ultrahigh gain coefficient in solution, we show for the first time that the gain cross sections of these CQWs is ≥3.3 × 10–14 cm2 in the green and ≥1.3 × 10–14 cm2 in the red, which are two orders of magnitude larger compared to those of CQDs.